CHA2DS2-VASc score and risk of thromboembolism and bleeding in patients with atrial fibrillation and recent cancer. (29th August 2020) - D'Souza, Maria; Carlson, Nicholas; Fosbøl, Emil; Lamberts, Morten; Smedegaard, Lærke; Nielsen, Dorte; Torp-Pedersen, Christian; Gislason, Gunnar; Schou, Morten
Abstract: Background: Cancer may influence the risk of thromboembolism and bleeding associated with the CHA2 DS2 -VASc score. We examined the risk of thromboembolism and bleeding associated with the CHA2 DS2 -VASc score in atrial fibrillation patients with and without recent cancer. Methods and results: Using nationwide registers all patients diagnosed with atrial fibrillation from 2000 to 2015 and not on oral anticoagulation or heparin therapy were included and followed for 2 years. Recent cancer was defined by a cancer diagnosis 5 years or fewer earlier. Risks of thromboembolism and bleeding were estimated in cumulative incidence curves and Cox regression models. We included 122, 053 patients with incident atrial fibrillation, 12, 014 (10%) had recent cancer. The 2-year cumulative incidence of thromboembolism and bleeding in patients with versus without recent cancer was 1.7% (95% confidence interval (CI) 0.5–2.8) and 4.3% (95% CI 2.4–6.2) versus 1.2% (95% CI 0.9–1.5) and 1.7% (95% CI 1.4–2.0) for CHA2 DS2 -VASc score 0; 3.2% (95%CI 2.2-4.3) and 4.4% (95%CI 3.2-5.6) versus 1.8% (95%CI 1.6-2.1) and 3.0% (95% CI 2.7–3.3) for CHA2 DS2 -VASc score 1; and 7.1% (95% CI 6.6–7.7) and 6.8% (95% CI 6.3–7.2) versus 10.9% (95% CI 10.7–11.1) and 6.2% (95% CI 6.1–6.4) for CHA2 DS2 -VASc score 2 or greater. Although the CHA2 DS2 -VASc score was associated with thromboembolism and bleeding in both patients with and without cancer, the association differed between the groups for thromboembolism (test for interaction, p < 0.001) and bleeding (test for interaction, p < 0.001). Conclusion: The association of the CHA2 DS2 -VASc score and risk of thromboembolism and bleeding differed between atrial fibrillation patients with and without recent cancer. Therefore, the CHA2 DS2 -VASc score should be used with caution in patients with recent cancer.